Tribal India - Raha, Manish Kumar, (ed.) (New Delhi, 1989)
The present book in two separate volumes, is no doubt an addition to a number of books on this theme so far published. But this book has the distinction of having articles on the general issues relating to the policies of the tribal welfare, the problems and development of our tribal brethren, area specific or state level issues, issues relating to the impact of the problems like industrialization, agricultural development, etc. and also on certain other specific issues. As a result our readers, the administrators, planners, social scientists, social workers, politicians and even the village level workers, will gather first-hand knowledge about the nature of problems and the extent of development taking place among the Scheduled Tribes of our country. The book will also help the tribal leaders to know what is happening in regard to their problems, and development. Further, this book, I believe, will be of in mense help to the students and scholars of Applied Anthropology. Considering the number of the articles selected for this book, I had to distribute them in two separate volumes. The present volume i.e. Volume One has given the vivid account on the policies regarding tribal development in general for India as a whole and for some States and Union Territories in particular.
Keywords: Community Development